The productive processing of formulaic sequences by second language learners in writing - Fan, Kunmeng; Wang, Haixiao (Frontiers in Psychology, 2024)
There has been much debate in psycholinguistic research on whether formulaic sequences (FSs) are processed holistically or in a compositional manner. Whereas most previous studies on this issue focused on the receptive processing of FSs, few have investigated the productive processing of FSs, particularly in the second language (L2) learning context. Besides, most previous studies on L2 FSs examined learner-external FSs, or those identified by external criteria such as corpus frequency with little attention to learner-internal FSs, or psychological units perceived as wholes by learners themselves, although there might be much overlap between learner-external and learner-internal FSs. This study was designed to explore the productive processing of FSs by L2 learners from their own perspective, while taking into account the effects of L2 proficiency and topic familiarity. It made a distinction between internal FSs and purely external FSs as the primary criterion of categorizing learners’ processing behaviors. Ten Chinese English learners from two proficiency levels completed two writing tasks differing in topic familiarity. Upon the completion of each task, each participant and the researcher identified the FSs separately and then distinguished internal FSs and purely external FSs (termed as assembled FSs, since they were perceived as being assembled from scratch) collectively. Next, each participant performed video stimulated recall (VSR) for the production process of each FS. The results showed that the learners’ conscious processing (i.e., retrieval/assembly and integration into the text) of FSs can be categorized on two levels (lexical and syntactic). There was more holistic processing than compositional processing on the lexical level, but not on the syntactic level, indicating the learners’ sizable storages of FSs and the syntactic flexibility of FSs. Furthermore, between-group differences and between-task differences were detected on two processing levels: higher-proficiency students retrieved more internal FSs and made more modifications to them than their lower-proficiency counterparts; in the familiar-topic writing, learners retrieved more internal FSs and made less modifications to them. Based on the findings, a model of L2 FS production is proposed, and pedagogical implications for the teaching of L2 FSs are provided.